Analysis in vitro of direct bonding system with cyanoacrylate ester and orthodontic wires - Manfrin, Thais Mara [UNESP]; Poi, Wilson Roberto [UNESP]; Mendonça, Marcos Rogério de [UNESP]; Cardoso, Leandro Carvalho [UNESP]; Marcal Massa Sundefeld, Maria Lucia; Sonoda, Celso Koogi [UNESP]; Barioni, Sônia Regina Panzarini [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The aim of this study was to evaluate the tensile strength of orthodontic wires bonded onto the enamel with cyanoacrylate ester. To obtain the specimens, 120 human premolars (extracted for orthodontic or periodontal reasons) were included in acrylic blocks of rapid polymerization with three teeth each. Four groups were formed with ten specimens each. In the specimens, a dental splint model was made with cyanoacrylate ester and round stainless steel wire. In groups I, II and III, cyanoacrylate ester was used with round steel wires, with variation in diameter: 0.014 inches; 0.016 inches and 0.018 inches, respectively. In group IV, round steel wire 0.018 inches was used with photo polymerizing resin composite with previous acid etching. The adhesive force of the materials was measured in two points under the action of the tensiometer (ETM-USA). The number of loose wires was counted along with those that remained fixed according to the different levels of force applied because of the direction of the tensile force (vertical or horizontal) and the diameter of the wire used. The data obtained were first submitted to a descriptive analysis and then submitted to a statistical analysis (Friedman's Test and Dunn's Test of Multiple Comparison - Epi-info 3.2). Within the limitations of the experimental conditions presented, the cyanoacrylate ester or 'Super Bonder (R)' maintained bonded to enamel and steel wires (0.016 and 0.018 inches) during the tensile strength tests under different levels of applied forces.